2022
DOI: 10.5194/essd-2022-47
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A past, present and future perspective on the European summer vapour pressure deficit

Abstract: Abstract. The response of evapotranspiration to anthropogenic warming is of critical importance to the water and carbon cycle. Con-flicting observations about changes of evapotranspiration stem mostly from the brevity of observations in time and space as well as a high degree of internal variability. Here we present the first gridded reconstruction of the European summer vapour pressure deficit (VPD) for the past four centuries. The gridded reconstruction is based on 26 European tree-ring oxygen iso-tope recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…Nonetheless, our study provides robust evidence for a strong link between summer aridity and maximum fire size as well as maximum burn severity across Europe. As continued increases in summer aridity are projected for Europe (Balting et al, 2022), we conclude that the stable development of area burned observed for Europe over the past decades will likely change to increased fire activity in the near future. Forest management and policy in Europe thus need to prepare for a future with larger and more severe fires, and develop strategies to mitigate fire-related impacts on forest carbon (Carnicer et al, 2022), resilience (Turner et al, 2022) and biodiversity (Palm et al, 2022).…”
Section: Discussion and Con Clus I On Smentioning
confidence: 86%
“…Nonetheless, our study provides robust evidence for a strong link between summer aridity and maximum fire size as well as maximum burn severity across Europe. As continued increases in summer aridity are projected for Europe (Balting et al, 2022), we conclude that the stable development of area burned observed for Europe over the past decades will likely change to increased fire activity in the near future. Forest management and policy in Europe thus need to prepare for a future with larger and more severe fires, and develop strategies to mitigate fire-related impacts on forest carbon (Carnicer et al, 2022), resilience (Turner et al, 2022) and biodiversity (Palm et al, 2022).…”
Section: Discussion and Con Clus I On Smentioning
confidence: 86%
“…It is consistent with climate modeling study showing SM‐temperature coupling was mostly related to multi‐decadal trends in SM, instead of its sub‐seasonal or interannual variability (e.g., concurrent dry‐hot conditions due to short‐term feedbacks or atmospheric driving conditions) (Vogel et al., 2017). Moreover, the summer VPD in WE and temperature were exhibited in‐phase coherencies at multi‐decadal frequencies since the 1800s (Figure S10 in Supporting Information , Balting et al., 2022), with a slightly earlier onset than the significant SM‐temperature relationship (Figure 3b). It probably implied that the increasing temperature drove up higher VPD and evapotranspiration first (Balting et al., 2022), leading to drier soil condition soon afterward.…”
Section: Discussionmentioning
confidence: 95%
“…June–July–August vapor pressure deficit (VPD) reconstruction since 1750 CE in WE (10°W–10°E, 40°N–55°N, 1° × 1°) was derived to investigate the VPD‐temperature relationship (Balting et al., 2022, https://doi.org/10.5281/zenodo.5958836). Besides, two millennia‐long tree‐ring reconstructions were compared with our reconstruction, namely the June–July–August scPDSI reconstruction for central Europe (Büntgen et al., 2021, https://www.ncdc.noaa.gov/paleo/study/32292) and June–July–August scPDSI gridded data in WE (10°W–10°E, 40°N–55°N, 0.5° × 0.5°) derived from the OWDA (E. R. Cook et al., 2015, https://www.ncdc.noaa.gov/paleo/study/19419).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations